An investigation of the chest radiographs in a controlled trial of busulphan, cyclophosphamide, and a placebo after resection for carcinoma of the lung. Issue 3 (June 1976) - Stott, H; Stephens, R; Fox, W; Simon, G; Roy, D C
Abstract : A standard series of radiographs of 588 patients allocated at random to treatment with busulphan (B patients), cyclophosphamide (C patients), or a placebo (P patients) for two years after surgery for bronchial carcinoma were viewed in three stages (following procedures which avoided bias) by an independent assessor, unaware of the allocated treatment of any patient, with a view to identifying pulmonary changes due to busulphan. Radiographic appearances consistent with busulphan lung were not reported in any of the 195 B patients (receiving a mean dosage of 464 mg of busulphan over 301 days) or of the 192 C patients but were present in one of the 201 patients receiving placebo.